(untitled) (Journal of Comparative Social Work, 2023)
In many countries, self-employment has become a common strategy for achieving inclusion in the labour market. Studies show that the occurrence of self-employment depends not only on individual motives, but also on existing policies and support. In Sweden, labour market measures to include people with disabilities are primarily organized to achieve inclusion through traditional forms of employment, though one tool offered by the Swedish Public Employment Service is Support to Start a Business. One part of this support is exclusive to people with disabilities. Although the Swedish Public Employment Service is responsible for this specific support, they collaborate with both external state-funded and non-profit actors who assess applicants’ business ideas. Drawing on the methodological approach of institutional ethnography, this article explores how the in-house frontline workers and external actors describe their professional roles, how they make decisions and what the chain of action looks like at multiple sites. Nine representatives from the various organizations that people can meet with when trying to start and run their own business have taken part in semi-structured interviews. The analysis identifies different institutional practices that overlap when people with disabilities apply for support to start their own business: one focusing on the efficient allocation of resources, and the other on the individual’s social and financial welfare by protecting the individuals these organizations meet with from risks connected to economy and health. These two practices reflect a long-standing conflict between control and support in objectives within both labour market policy and social work. This support of self-employment for people with disabilities is organized by actors who traditionally have not been studied in research on social work.